Electrochemical and UV-visible spectroscopic investigation of anthranilic acid interaction with DNA - Fatima Allouche; Nabil Benyza; Elhafnaoui Lanez; Abdelkader Chouaih; Touhami Lanez (Journal of Electrochemical Science and Engineering)
The interaction between anthranilic acid (Aa) and DNA was studied by cyclic voltammetry and UV-visible spectroscopy. Cisplatin (Cis), a drug that is known to interact with DNA, was used as a reference. The electrochemical response showed that the anodic peak potential of Aa shifted downward by 35.1 mV (from 934.4 to 899.3 mV) in the presence of DNA (18 µM). The shift suggests the occurrence of electrostatic interactions between Aa and the DNA backbone. Binding constant (7.08×104 M⁻¹) and free energy (-26.85 kJ mol-1) for Aa-DNA were derived from suppressed anodic peak current density, while Cis was found to have stronger binding (19.49×10⁴ M⁻¹) under identical conditions. UV-visible spectroscopy confirmed hypochromicity at 324 nm for Aa, which is consistent with groove binding, while the distinct mechanism of Cis most likely involves covalent cross-linking. Larger binding site size of Aa (5.76 base pairs) and decreased diffusion coefficients compared with Cis smaller footprint (0.56 base pairs), pointed to differences in mechanisms. These results highlight anthranilic acid as a promising DNA-targeting agent with potential applications in antimicrobial and anticancer drug development, providing a comparative context with the well-established pharmacology of cisplatin.